STRATEGI PERUSAHAAN BIDANG KONSTRUKSI DALAM MENGHADAPI RESESI EKONOMI: Studi Kasus PT ADHI KARYA (Persero) Tbk - Pandoyo; Yesi Pramesti; Iqna Tulhanifah (CV ODIS, 2021)
The rapid development in all fields creates business opportunities, especially in the construction sector. Construction involves various aspects of development, such as housing construction to roads. The purpose of this paper is to determine the strategic position of the company in the construction industry, to be able to get opportunities and survive the competition and survive the economic recession. In addition, it identifies the factors that affect company performance and develops strategic management so that the company can make decisions appropriately following company conditions. The national construction industry market, mostly dominated by large contractors who are members of the Indonesian Contractors Association (AKI), are members of 100 companies. Of the 100 AKI members, there are 10 national contractors, namely six BUMN, two quasi BUMN, and two national private companies. The sales level of the 10 large national contractors have almost the same income, so the level of competition is fierce. Competition in the construction service industry is getting tighter and the Covid 19 pandemic also has an impact on the development project of PT Adhi Karya. To deal with the recession that will occur, PT Adhi Karya has many specific strategies to deal with recession by implementing incentive strategies, related diversification strategies, providing training for HR, and disciplining SOPs and SWOT analysis.